FEMINISME DALAM NOVEL MOMOYE MEREKA MEMANGGILKU KARYA EKA HENDRA DAN KOICHI KIMURA - Ninuk Eri Jayanti; Chairil Effendy; A. Totok Priyadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractA novel entitled Momoye Mereka Memanggilku written by Eka Hindra and Koichi Kimura was published in 2007 by Erlangga Publishers in Jakatra. This novel told about the oppression carried out by the Japanese to Indonesian women in the Dutch colonial era. The oppression experienced by women in this novel can be studied with the study of feminism. The problems in this study were how the forms of gender inequality in women characters, how the forms of struggle of women characters in a novel entitled Momoye Mereka Memanggilku written by Eka Hindra and Koichi Kimura, and how the design of the results of this study on literary learning in university. From the research, it was found that there are 34 forms of violence and 26 forms of struggle in the novel entitled Momoye Mereka Memanggilku written by Eka Hindra and Koichi Kimura. The implementation of this learning of research is realized by making RPS and RPM. Keywords: novel Momoye Mereka Memanggilku, feminism, form of violence, form                  of struggle.